Design and fabrication of two degree of freedom free vibration test rig : coordinate coulping - Tan, Soon Wea (2013)
This thesis shows the design and fabrication of a vibration test rig with two degree of freedom free vibration in coordinate coupling. The objective for this project is to design and fabricate lab test rig for free vibration in coordinate coupling. Basically, the vibration test rig applied with the dynamic concept such as angular displacement, angular velocity, frequency, two degree of freedom and free vibration. Design generation of the test rig is portrayed and three dimensional view as well as orthographic view was done using Solidworks software. The needed fabrication process is briefly described and the main material used in this project is aluminium and mild steel. Process like cutting, drilling, grinding, tapping and etc is needed to fabricate the test rig. Some methods of improvement for the combination of test rig are also provided for further improvement of the test rig. Finally the test rig can experiment to test the coordinate coupling theory of vibration.